Priv.-Doz. Dr. med. Rainer B. Zotz - Scharf, Rüdiger E. (Hämostaseologie, 2023)
It is with great sadness and deep grief that we received news about the sudden death of Priv.-Doz. Dr. Rainer Bernd Zotz (Fig. 1). He was torn out of life on September 26, 2022 by suffering from an acute illness. As his long-standing mentor and colleague, it is my sad duty to write this obituary.